Multidisciplinary Rehabilitation in Oesophago-gastric Cancer Surviorship - O'NEILL, LINDA MARIE (Trinity College Dublin. School of Medicine. Discipline of Physiotherapy, 2018)
As survival rates for oesophageal and gastric cancer slowly improve, there has been an emergence of a unique cohort of cancer survivors who present with multifaceted nutritional and physical needs which are amenable to rehabilitative measures. Multidisciplinary rehabilitation in oesophago-gastric cancer has been under explored and accordingly, this thesis aimed to examine i) the feasibility, ii) the efficacy of multidisciplinary rehabilitation in oesophago-gastric cancer survivorship. Study I of this thesis established the feasibility of a 12 week multidisciplinary rehabilitation consisting of supervised and homebased exercise sessions, 1:1 dietary counselling, and group education sessions. Feasibility was demonstrated by the recruitment rate, adherence rates to exercise sessions, lack of adverse events, and positive improvements in cardiorespiratory fitness (VO2max), physical performance (six minute walk test), and global health related quality of life (HRQOL). Importantly, body composition remained stable during the 12 week programme. Study II further investigated the efficacy of the 12 week multidisciplinary rehabilitation programme by Randomised Controlled Trial. The study was powered to detect a change in the primary outcome cardiorespiratory fitness (VO2max). Participants were randomised to a usual care control group (n=22), or intervention group (n=21). Accounting for baseline values, the intervention group experienced statistically significant improvements in VO2max compared to the control group upon completion of the 12 week programme and at 3 month follow-up. As per Study I, body composition remained stable. No changes were observed in any of the secondary measures (six minute walk test, hand grip strength, 1-repitition max, accelerometer measured activity levels, and HRQOL). Study III utilized qualitative methods to explore the challenges faced in returning to physical activity in the first 6 months of recovery post-oesophagogastric cancer surgery. Participants in Study III identified a myriad of issues which are barriers to returning to physical activity post-oesophagogastric surgery, and also reported the need for rehabilitative interventions in the first six months of recovery. The results of this thesis highlight that multidisciplinary rehabilitation is effective, safe, and achievable in this complex cohort.
APPROVED
Keywords: Oesophageal Cancer; Gastric Cancer; Rehabilitation